1994
DOI: 10.2307/2152736
|View full text |Cite
|
Sign up to set email alerts
|

Heights of Projective Varieties and Positive Green Forms

Abstract: The pairing CH (X) x Z.(X) ~ CH (Spec(&'K))Q 2.3.1. Definition and basic properties 2.3.2. Arakelov varieties and arithmetic fundamental classes 2.3.3. External products 2.3.4. Degrees 3. The height of cycles defined by an hermitian line bundle 3.1. Definition and examples 3.1.1. The height hr 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
216
0
31

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(250 citation statements)
references
References 0 publications
3
216
0
31
Order By: Relevance
“…We call U a quasi-potential of S. We have in fact the following more precise result [53]. The construction of U uses a kernel constructed in Bost-Gillet-Soulé [17]. We call U the Green quasi-potential of S. When p = 1, two quasi-potentials of S differ by a constant.…”
Section: Fsmentioning
confidence: 99%
“…We call U a quasi-potential of S. We have in fact the following more precise result [53]. The construction of U uses a kernel constructed in Bost-Gillet-Soulé [17]. We call U the Green quasi-potential of S. When p = 1, two quasi-potentials of S differ by a constant.…”
Section: Fsmentioning
confidence: 99%
“…-This definition is the natural extension to metrized Rdivisor of the height functions of points from Arakelov geometry as in [7,30,18,12,11]. Observe that, to define the height of cycles of arbitrary dimension in [11], we need the variety to be proper and the metrics to be DSP, but these conditions are not needed in the case of points.…”
Section: Successive Minima Of Toric Metrized R-divisorsmentioning
confidence: 99%
“…Let m and n be positive integers, f and g be generic univariate polynomials of degrees m and n respectively: (1) f (x) := f 0 + f 1 x + · · · + f m x m , g(x) := g 0 + g 1 x + · · · + g n x n .…”
Section: Introductionmentioning
confidence: 99%
“…The sharpest upper bound for the height was given in [10, Theorem 1.1], where it is shown that H (Res(f, g)) ≤ (m+ 1) n (n+ 1) m . Previous upper bounds were given in [1,6,7,8,11], for more general resultants which include R(f, g).…”
Section: Introductionmentioning
confidence: 99%